A Generation of Excellence - Brown, Robert Craig, 1935- (Book collections on Project MUSE., 2007)
The Canadian Institute for Advanced Research originated at the University of Toronto in the early 1980s. Since that time, it has gone from a small, independent centre to an important and revered institution with a significant role in the study of sciences, social sciences, and humanities in Canada. A Generation of Excellence is a detailed history of the CIAR from its humble beginnings to its ascension as one of the most important research organizations in the country.Beginning in the summer of 1982, with the CIAR merely a conception in the minds of senior scholars at the University of Toronto, Craig Brown takes us through the process of realization, detailing the early years of the Institute under the presidency of Dr. Fraser Mustard. From early struggles to eventual triumphs, Brown examines the CIAR?s pursuit of an ethos ? to explore fundamental issues in the social sciences and humanities by funding teams of researchers ? showing how success was painstakingly achieved. The rise of the CIAR is deftly illustrated by pairing its earliest projects with the twentieth anniversary Congress held in 2002 in honour of the Institute and two decades of research.A Generation of Excellence tells the story of one of the country?s most remarkable institutions.